Preparation method of silicon dioxide gel, crucible and preparation method of crucible
By adding silicone source and deionized water to the organic solvent, adding moisturizer and crosslinking agent to adjust the pH value, and finally aging it while standing to obtain a high-purity silica gel, solving the problem of limited production capacity of high-purity quartz sand, providing high-performance materials for the photovoltaic industry, extending the service life of the crucible, and saving the use of high-purity quartz sand.
Patent Information
- Application Number
- CN202411868375.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-21
AI Technical Summary
The production capacity of high-purity quartz sand suitable for the photovoltaic industry in the prior art is limited and it is difficult to meet the market usage demand.
By adding a silicone source and deionized water to the organic solvent, a second matrix solution is formed, and a humectant and a crosslinking agent are added therein to form an intermediate solution, and then the pH value is adjusted to form a mixed solution, and finally aged in a stand-alone to obtain a silica gel. The gel has high purity and excellent performance, and is suitable for the photovoltaic industry.
The preparation of high-purity silica gel is realized, the problem of limited production capacity of high-purity quartz sand is solved, and high-performance materials are provided for the photovoltaic industry, which extends the service life of the crucible and saves the use of high-purity quartz sand.
Smart Images

Figure CN119660751A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of crucible preparation, and in particular to a method for preparing silica gel, a crucible and a method for preparing the same. Background Art
[0002] High-purity quartz sand usually refers to quartz sand with a silicon dioxide content higher than 99.98%. It has excellent physical and chemical properties such as high temperature resistance, corrosion resistance, high strength, high light transmittance, and low thermal expansion coefficient. It is widely used in semiconductors, fiber optic communications, photovoltaics, optics, electro-light sources and other fields. It is an important support for strategic emerging industries and an irreplaceable material.
[0003] Among them, the main application of high-purity quartz sand in photovoltaics is quartz crucible. Quartz crucible is a container for containing silicon liquid during crystal pulling. During crystal pulling, the inner surface of the quartz crucible is in direct contact with the molten polysilicon material, and has high performance (purity / gas flame inclusions / particle size distribution / consistency) requirements. Once there are too many bubbles or impurities are precipitated, it will have a greater negative impact on crystal pulling. Therefore, at present, quartz crucibles are usually replaced after working continuously for 300-400 hours at about 1500°C. They have a limited service life and are high-cost consumables.
[0004] With the large-scale development of the photovoltaic industry, the market demand for high-purity quartz sand is also increasing. However, due to the scarcity of high-purity quartz sand resources and the high technical threshold for quartz sand purification, the production capacity of high-purity quartz sand suitable for the photovoltaic industry is limited, making it difficult to meet its usage demand. Summary of the invention
[0005] The purpose of the present application is to provide a method for preparing silica gel, a crucible and a method for preparing the same in view of the deficiencies in the above-mentioned prior art, by adding an organic silicon source and deionized water to an organic solvent to form a second matrix solution, and adding a moisturizing agent and a cross-linking agent to the second matrix solution and stirring evenly to form an intermediate solution, and then adding an acid solution or an alkaline solution for adjusting the pH value of the intermediate solution to the intermediate solution and stirring evenly to form a mixed solution, and letting the mixed solution stand and age to obtain silica gel. The silica gel has high purity and excellent performance and can be widely used in the photovoltaic industry to solve the problem of limited production capacity and insufficient supply of high-purity quartz sand suitable for the photovoltaic industry in the prior art.
[0006] To achieve the above purpose, the technical solution adopted in the embodiment of the present application is as follows:
[0007] The present invention provides a method for preparing silica gel, which comprises:
[0008] Preparing a second matrix solution: adding an organic silicon source and deionized water into an organic solvent to form a second matrix solution;
[0009] Prepare an intermediate solution: add a moisturizer and a cross-linking agent to the second base solution and stir evenly to form an intermediate solution;
[0010] Preparing a mixed solution: adding an acid solution or an alkaline solution for adjusting the pH value of the intermediate solution to the intermediate solution and stirring the solution to form a mixed solution;
[0011] Obtaining silica gel: allowing the mixed solution to stand and age to obtain silica gel.
[0012] Optionally, preparing the second matrix solution comprises:
[0013] Preparing a first matrix solution: mixing an organic silicon source, an organic solvent and deionized water and stirring them uniformly to form a first matrix solution;
[0014] Improving the first matrix solution: adding a reinforcing agent to the first matrix solution and stirring the solution uniformly to form a second matrix solution, wherein the density of the second matrix solution is greater than that of the first matrix solution.
[0015] Optionally, in preparing the first matrix solution, the mass ratio of the organosilicon source, the organic solvent and the deionized water is (25-35): (80-120): (80-120).
[0016] Optionally, when the first matrix solution is improved, the mass ratio of the first matrix solution to the reinforcing agent is (185-275): (10-15).
[0017] Optionally, in preparing the intermediate solution, the mass ratio of the second matrix solution, the humectant and the cross-linking agent is (195-290): (2-3): (2-3).
[0018] Optionally, in preparing the mixed solution, an acid solution is added to the intermediate solution to adjust the pH value of the intermediate solution to 1-3.
[0019] Optionally, the organosilicon source is tetraethyl orthosilicate.
[0020] Optionally, the organic solvent is anhydrous ethanol or methanol.
[0021] Optionally, the reinforcing agent is silicon dioxide or silicon nitride.
[0022] Optionally, the humectant is carboxamide or glycerin.
[0023] Optionally, the cross-linking agent is polyethylene glycol.
[0024] Optionally, in preparing the second matrix solution, in preparing the intermediate solution, and / or in preparing the mixed solution, the stirring temperature is 40-60°C.
[0025] Optionally, in preparing the mixed solution, the stirring time is 6 to 8 hours;
[0026] And / or, the silica gel is obtained and the aging time is 4 to 6 hours.
[0027] The embodiment of the present application also provides a silica gel, which is prepared by any of the above-mentioned methods for preparing silica gel, wherein a moisturizer and a cross-linking agent are added during the preparation process of the silica gel.
[0028] The present application also provides a method for preparing a crucible, the method comprising:
[0029] Placing the crucible base in the mold so that a first gap exists between the mold and the inner wall surface of the crucible base;
[0030] Pour the silica gel prepared by any of the above-mentioned methods for preparing silica gel into the mold along the first gap, so that the silica gel is coated on the inner wall surface of the crucible base, wherein a moisturizing agent and a cross-linking agent are added during the preparation of the silica gel;
[0031] The crucible substrate coated with silica gel is placed in a heat treatment furnace for heat treatment to melt the silica gel, and then the melted silica gel is cooled to form a silica coating on the inner wall surface of the crucible substrate.
[0032] Optionally, pouring the silica gel prepared by any of the above-mentioned methods for preparing silica gel into the mold along the first gap includes: pouring the silica gel into the mold multiple times, and drying the silica gel after each pouring, and repeating multiple times so that the silica gel is coated on the inner wall surface of the crucible base.
[0033] Optionally, placing the crucible substrate coated with silica gel in a heat treatment furnace for heat treatment to melt the silica gel, and then cooling the melted silica gel to form a silica coating on the inner wall surface of the crucible substrate, including: placing the crucible substrate coated with silica gel in a muffle furnace, raising the temperature to 200-250°C at 0.5-2°C / min, keeping the temperature for 20-40min, then raising the temperature to 500-700°C at 5-10°C / min, keeping the temperature for 60-100min to melt the silica gel, and then naturally cooling the melted silica gel to room temperature to form a silica coating on the inner wall surface of the crucible substrate.
[0034] Optionally, the thickness of the silicon dioxide coating ranges from 1 to 3 mm.
[0035] Optionally, before placing the crucible base in the mold and providing a first gap between the mold and the inner wall surface of the crucible base, the method further comprises: performing a surface roughening treatment on the inner wall surface of the crucible base.
[0036] Optionally, roughening the inner wall surface of the crucible base includes: spraying sandblasting particles with a particle size range of 22 to 40 meshes onto the inner wall surface of the crucible base by compressed air with a pressure of 0.3 to 0.6 MPa, and removing residual sandblasting particles on the surface.
[0037] Optionally, before performing surface roughening treatment on the inner wall surface of the crucible base, the method further comprises: ultrasonically cleaning the crucible base and drying it at 60° C. to 100° C.
[0038] An embodiment of the present application also provides a crucible, which is prepared using any of the above-mentioned crucible preparation methods. The crucible includes a crucible base and a silica coating formed on the inner wall of the crucible base by melting and cooling silica gel, wherein a moisturizer and a cross-linking agent are added during the preparation of the silica gel.
[0039] The embodiment of the present application also provides an application of the above-mentioned crucible in the process of preparing single crystal silicon.
[0040] The beneficial effects of this application include:
[0041] The present application provides a silica gel and a preparation method thereof. The preparation method of the silica gel comprises: adding an organic silicon source and deionized water into an organic solvent to form a second matrix solution; adding a moisturizer and a cross-linking agent into the second matrix solution and stirring the solution uniformly to form an intermediate solution; adding an acid solution or an alkaline solution for adjusting the pH value of the intermediate solution into the intermediate solution and stirring the solution uniformly to form a mixed solution; and allowing the mixed solution to stand and age to obtain the silica gel. The present application forms a second matrix solution by first adding an organic silicon source and deionized water to an organic solvent. At this time, the main component of the second matrix solution is silicon dioxide. A humectant and a cross-linking agent are added to the second matrix solution and stirred evenly. The second matrix solution reacts with the humectant and the cross-linking agent to form an intermediate solution to improve the strength and structural stability of silicon dioxide. Then, an acid solution or an alkaline solution is added to the intermediate solution and stirred evenly to control the reaction rate and form a mixed solution with a relatively small pore size. The mixed solution is allowed to stand and age so that different compounds in the mixed solution can react fully and evenly to obtain a silica gel. The silica gel has high purity, high strength, stable structure, and small pore size, and is easy to combine with the inner wall surface of the crucible matrix to form a dense silica coating. When a single crystal silicon rod is pulled by a continuous straight pulling method using a crucible with this coating, the content of metal ion impurities such as magnesium, aluminum, and yttrium in the silicon rod can be reduced from 100ppm to about 10ppm, which can be widely used in the photovoltaic crystal pulling industry.
[0042] In addition, the present application also provides a crucible and a preparation method thereof, the preparation method of the crucible comprising: placing a crucible base in a mold, and allowing a first gap to exist between the mold and the inner wall surface of the crucible base; pouring the silica gel prepared by any of the above-mentioned methods for preparing silica gel into the mold along the first gap, so that the silica gel is coated on the inner wall surface of the crucible base, wherein a moisturizing agent and a cross-linking agent are added during the preparation of the silica gel; placing the crucible base coated with the silica gel in a heat treatment furnace for heat treatment, so that the silica gel is melted, and then cooling the melted silica gel to form a silica coating on the inner wall surface of the crucible base. By combining the above-mentioned silica gel with the inner wall surface of the crucible substrate to form a dense silica coating, when a single crystal silicon rod is pulled by the continuous straight pulling method, this coating can isolate the molten silicon liquid from direct contact with the crucible substrate, and block the diffusion of metal elements and other impurity elements in the crucible substrate into the silicon liquid, without affecting the production of silicon rods. At the same time, the service life of the crucible can be extended, and the preparation process is simple. In addition, by forming a silica coating on the inner wall surface of the crucible substrate, there is no need to use a crucible made of all quartz material. Each crucible prepared can save 20-30kg of high-purity quartz sand, which can effectively alleviate the current situation of quartz sand in short supply. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0044] Figure 1 A flow chart of a method for preparing silica gel provided in an embodiment of the present application;
[0045] Figure 2 A flow chart of a method for preparing a second matrix solution provided in an embodiment of the present application;
[0046] Figure 3 A flow chart of a method for preparing a crucible provided in an embodiment of the present application. DETAILED DESCRIPTION
[0047] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The components of the embodiments of the present application described and shown in the drawings here can be arranged and designed in various different configurations.
[0048] Therefore, the following detailed description of the embodiments of the present application provided in the accompanying drawings is not intended to limit the scope of the present application for protection, but merely represents selected embodiments of the present application. It should be noted that, in the absence of conflict, the various features in the embodiments of the present application can be combined with each other, and the combined embodiments are still within the scope of protection of the present application.
[0049] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.
[0050] like Figure 1 As shown, the present application embodiment provides a method for preparing silica gel, the method comprising:
[0051] S210: preparing a second matrix solution: adding an organic silicon source and deionized water into an organic solvent to form a second matrix solution;
[0052] S220: preparing an intermediate solution: adding a moisturizing agent and a cross-linking agent to the second base solution and stirring the solution to form an intermediate solution;
[0053] S230: preparing a mixed solution: adding an acid solution or an alkaline solution for adjusting the pH value of the intermediate solution to the intermediate solution and stirring the mixture to form a mixed solution;
[0054] S240: Obtaining silica gel: allowing the mixed solution to stand and age to obtain silica gel.
[0055] Specifically, the present application forms a second matrix solution by first adding an organic silicon source and deionized water to an organic solvent. At this time, the main component of the second matrix solution is silicon dioxide. A humectant and a cross-linking agent are added to the second matrix solution and stirred evenly. The second matrix solution reacts with the humectant and the cross-linking agent to form an intermediate solution, thereby improving the strength and structural stability of the silicon dioxide. An acid solution or an alkaline solution is then added to the intermediate solution and stirred evenly to control the reaction rate and form a mixed solution with a relatively small pore size. The mixed solution is allowed to stand and age so that different compounds in the mixed solution can react fully and evenly to obtain a silicon dioxide gel. The silicon dioxide gel has high purity, high strength, stable structure, and small pore size. It is easy to combine with the inner wall surface of the crucible matrix to form a dense silicon dioxide coating, and can be widely used in the photovoltaic industry to solve the problem of limited production capacity and insufficient supply of high-purity quartz sand suitable for the photovoltaic industry in the prior art.
[0056] It should be noted that adding a moisturizer to the second matrix solution can reduce the capillary force during the drying process, reduce the drying stress, and improve the strength of the silica; adding a cross-linking agent to the second matrix solution can make the silica easier to disperse and prevent the aggregation and sedimentation of the silica, and can also undergo a cross-linking reaction with other polymers to form cross-linking points, making the final silica gel structure more stable; adding an acid solution or an alkaline solution to the intermediate solution can adjust the reaction rate. If the reaction proceeds in the direction of generating an acidic solution, when the reaction rate needs to be inhibited, an acid solution can be added to lower the pH value. When the reaction rate needs to be promoted, an alkaline solution can be added to increase the pH value; if the reaction proceeds in the direction of generating an alkaline solution, when the reaction rate needs to be inhibited, an alkaline solution can be added to increase the pH value. When the reaction rate needs to be promoted, an acid solution can be added to lower the pH value.
[0057] In the present application, it is preferred to add an acid solution to the intermediate solution. Under acidic conditions, the gelation time is mainly controlled by the polymerization rate. The polymerization rate slows down as the pH value decreases, which prolongs the gelation time and avoids the stress difference caused by the different solvent evaporation rates between the inner layer and the surface layer. This is beneficial to alleviate the cracking of the silica gel during the drying process. In addition, the addition of the acid solution is beneficial to the preparation of silica gel with relatively small pore size, lower sintering temperature and fewer pores, so that it is easy to combine with the inner wall surface of the crucible substrate to form a dense silica coating.
[0058] It should be understood that the present application does not limit the order of implementation of S210 and S220, and S210 and S220 can be performed simultaneously, or S210 can be completed first, then S220, and then S240. However, it should be noted that S230 needs to be implemented after both S210 and S220 are completed, and then S240 can be implemented after S230 is completed.
[0059] Alternatively, if Figure 2 As shown, preparing the second matrix solution includes:
[0060] S211: preparing a first matrix solution: mixing an organic silicon source, an organic solvent and deionized water and stirring them uniformly to form a first matrix solution;
[0061] S212: improving the first matrix solution: adding a reinforcing agent to the first matrix solution and stirring the solution evenly to form a second matrix solution, wherein the density of the second matrix solution is greater than that of the first matrix solution.
[0062] It should be understood that the present application does not limit the order of implementing S211 and S212. S211 and S212 can be performed simultaneously, or S211 can be completed first and then S212.
[0063] It should be noted that adding a reinforcing agent to the first matrix solution can reduce the number of silica pores in the first matrix solution, reduce the pore size, increase the density, reduce the high temperature shrinkage of silica, and increase the content, strength and bonding strength of silica.
[0064] Optionally, the organic silicon source may be one or more of methyl orthosilicate, ethyl orthosilicate, tetraethyl orthosilicate, tetrabutyl orthosilicate, and alkoxysilane.
[0065] Optionally, the organic solvent may be one or more of anhydrous ethanol, methanol, propanol, isopropanol, butanol, isobutanol, ethylene glycol, propylene glycol, diethylene glycol, butanediol, diacetone alcohol, glycerol, and diethylene glycol.
[0066] Optionally, the humectant is carboxamide or glycerin.
[0067] Optionally, the cross-linking agent is polyethylene glycol.
[0068] Optionally, the reinforcing agent is silicon dioxide or silicon nitride. Preferably, the reinforcing agent is nano-fumed silicon dioxide.
[0069] Optionally, the acid solution can be one or more of hydrochloric acid, hypochlorous acid, perchloric acid, sulfuric acid, nitric acid, phosphoric acid, hydrofluoric acid, hydroiodic acid, hydrobromic acid, oxalic acid, acetic acid, acetic acid, oxalic acid, sulfurous acid, pyruvic acid, nitrous acid, lactic acid, benzoic acid, acrylic acid, propionic acid, hydrosulfuric acid, and oleic acid.
[0070] Alternatively, the alkaline solution can be ammonia water, sodium hydroxide, ammonium fluoride, ammonium bicarbonate, sodium carbonate, sodium bicarbonate, ethanolamine, diethanolamine, triethanolamine, methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, ethylenediamine, propylamine, dipropylamine, tripropylamine, isopropylamine, diisopropylamine, 1,2-dimethylpropylamine, 1,2-propylenediamine, 2-propyleneamine, cyclopropylamine, n-butylamine, di-n-butylamine, isobutylamine, sec-butylamine, 1,4-butylenediamine, diisobutylamine, hexylamine, 2-ethylhexylamine, hexylenediamine, monoethanolamine, One or more of diethanolamine, triethanolamine, 3-propanolamine, isopropanolamine, diisopropanolamine, triisopropanolamine, N,N-methyldiethanolamine, N,N-diethylethanolamine, diethylenetriamine, hexamethylenetetramine, hexamethyleneimine, triethylenediamine, cyclohexyleneimine, morpholine, piperazine, cyclohexylamine, aniline, diphenylamine, benzidine, o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, o-methylaniline, m-methylaniline, p-methylaniline, 2,3-dimethylaniline, 1-naphthylamine, 2-naphthylamine and naphthalenediamine.
[0071] In the present application, an example is given in which the organosilicon source is tetraethyl orthosilicate, the organic solvent is anhydrous ethanol, the moisturizing agent is formamide, the cross-linking agent is polyethylene glycol, the reinforcing agent is nano-fumed silica, and the acid solution is hydrochloric acid.
[0072] Embodiment 1:
[0073] Optionally, tetraethyl orthosilicate, anhydrous ethanol and deionized water are mixed and stirred evenly to form a first matrix solution, in which the mass ratio of tetraethyl orthosilicate, anhydrous ethanol and deionized water is 25:80:80.
[0074] Optionally, nano-gas-phase silica is added to the first matrix solution and stirred evenly to form a second matrix solution, and the mass ratio of the first matrix solution to the nano-gas-phase silica is 185:10.
[0075] Optionally, formamide and polyethylene glycol are added to the second matrix solution and stirred evenly to form an intermediate solution, in which the mass ratio of the second matrix solution, formamide and polyethylene glycol is 195:2:2.
[0076] Optionally, an acid solution or an alkaline solution for adjusting the pH value of the intermediate solution is added to the intermediate solution and stirred evenly to form a mixed solution, and hydrochloric acid is added to the intermediate solution to adjust the pH value of the intermediate solution to 3.
[0077] Optionally, tetraethyl orthosilicate and deionized water are added to anhydrous ethanol to form a second matrix solution, and the stirring temperature is 40°C.
[0078] Optionally, formamide and polyethylene glycol are added to the second matrix solution and stirred evenly to form an intermediate solution, and the stirring temperature is 40°C.
[0079] Optionally, an acid solution or an alkaline solution for adjusting the pH value of the intermediate solution is added to the intermediate solution and stirred evenly to form a mixed solution, and the stirring temperature is 40°C.
[0080] Optionally, an acid solution or an alkaline solution for adjusting the pH value of the intermediate solution is added to the intermediate solution and stirred evenly to form a mixed solution. The stirring time is 6 hours.
[0081] Optionally, the mixed solution is allowed to stand and age to obtain a silica gel, and the aging time is 4 hours.
[0082] Embodiment 2:
[0083] Optionally, tetraethyl orthosilicate, anhydrous ethanol and deionized water are mixed and stirred evenly to form a first matrix solution, in which the mass ratio of tetraethyl orthosilicate, anhydrous ethanol and deionized water is 30:100:100.
[0084] Optionally, nano-gas-phase silica is added to the first matrix solution and stirred evenly to form a second matrix solution, and the mass ratio of the first matrix solution to the nano-gas-phase silica is 230:12.
[0085] Optionally, formamide and polyethylene glycol are added to the second matrix solution and stirred evenly to form an intermediate solution, in which the mass ratio of the second matrix solution, formamide and polyethylene glycol is 242:2:2.
[0086] Optionally, an acid solution or an alkaline solution for adjusting the pH value of the intermediate solution is added to the intermediate solution and stirred evenly to form a mixed solution, and hydrochloric acid is added to the intermediate solution to adjust the pH value of the intermediate solution to 2.
[0087] Optionally, tetraethyl orthosilicate and deionized water are added to anhydrous ethanol to form a second matrix solution, and the stirring temperature is 50°C.
[0088] Optionally, formamide and polyethylene glycol are added to the second matrix solution and stirred evenly to form an intermediate solution, and the stirring temperature is 50°C.
[0089] Optionally, an acid solution or an alkaline solution for adjusting the pH value of the intermediate solution is added to the intermediate solution and stirred evenly to form a mixed solution, and the stirring temperature is 50°C.
[0090] Optionally, an acid solution or an alkaline solution for adjusting the pH value of the intermediate solution is added to the intermediate solution and stirred evenly to form a mixed solution. The stirring time is 7 hours.
[0091] Optionally, the mixed solution is allowed to stand and age to obtain a silica gel, and the aging time is 5 hours.
[0092] Embodiment 3:
[0093] Optionally, tetraethyl orthosilicate, anhydrous ethanol and deionized water are mixed and stirred evenly to form a first matrix solution, in which the mass ratio of tetraethyl orthosilicate, anhydrous ethanol and deionized water is 35:120:120.
[0094] Optionally, nano-gas-phase silica is added to the first matrix solution and stirred evenly to form a second matrix solution, and the mass ratio of the first matrix solution to the nano-gas-phase silica is 275:15.
[0095] Optionally, formamide and polyethylene glycol are added to the second matrix solution and stirred evenly to form an intermediate solution, in which the mass ratio of the second matrix solution, formamide and polyethylene glycol is 290:3:3.
[0096] Optionally, an acid solution or an alkaline solution for adjusting the pH value of the intermediate solution is added to the intermediate solution and stirred evenly to form a mixed solution, and hydrochloric acid is added to the intermediate solution to adjust the pH value of the intermediate solution to 1.
[0097] Optionally, tetraethyl orthosilicate and deionized water are added to anhydrous ethanol to form a second matrix solution, and the stirring temperature is 60°C.
[0098] Optionally, formamide and polyethylene glycol are added to the second matrix solution and stirred evenly to form an intermediate solution, and the stirring temperature is 60°C.
[0099] Optionally, an acid solution or an alkaline solution for adjusting the pH value of the intermediate solution is added to the intermediate solution and stirred evenly to form a mixed solution, and the stirring temperature is 60°C.
[0100] Optionally, an acid solution or an alkaline solution for adjusting the pH value of the intermediate solution is added to the intermediate solution and stirred evenly to form a mixed solution. The stirring time is 8 hours.
[0101] Optionally, the mixed solution is allowed to stand and age to obtain a silica gel, and the aging time is 6 hours.
[0102] The embodiment of the present application also provides a silica gel, which is prepared by any of the above-mentioned methods for preparing silica gel, wherein a moisturizer and a cross-linking agent are added during the preparation of the silica gel. The silica gel has high purity, high strength, stable structure, and small pore size. It is easy to combine with the inner wall surface of the crucible substrate to form a dense silica coating, and can be widely used in the photovoltaic industry.
[0103] like Figure 3 As shown, the embodiment of the present application also provides a method for preparing a crucible, the method comprising:
[0104] S100: placing the crucible base in a mold, and allowing a first gap to exist between the mold and the inner wall surface of the crucible base;
[0105] S200: pouring the silica gel prepared by any of the above-mentioned methods for preparing silica gel into the mold along the first gap so that the silica gel is coated on the inner wall surface of the crucible base, wherein a moisturizing agent and a cross-linking agent are added during the preparation of the silica gel;
[0106] S300: placing the crucible substrate coated with silica gel in a heat treatment furnace for heat treatment to melt the silica gel, and then cooling the melted silica gel to form a silica coating on the inner wall surface of the crucible substrate.
[0107] It should be understood that the crucible base can be a silicon carbide crucible, a silicon nitride crucible, a zirconia crucible, or other crucibles used to hold silicon liquid when preparing silicon wafers by continuous vertical pulling single crystal method. The present application does not limit the type of crucible base. By combining the above-mentioned silica gel with the inner wall surface of the crucible base to form a dense silica coating, when the single crystal silicon rod is pulled by continuous vertical pulling method, this coating can isolate the direct contact between the molten silicon liquid and the crucible base, and block the metal elements and other impurity elements in the crucible base from diffusing into the silicon liquid, which does not affect the production of silicon rods. At the same time, it can extend the service life of the crucible, and the preparation process is simple, which can effectively alleviate the current situation of quartz sand in short supply.
[0108] Optionally, the size of the crucible base is in the range of 14 to 36 inches, preferably, in the range of 28 to 36 inches.
[0109] Optionally, pouring the silica gel prepared by any of the above-mentioned methods for preparing silica gel into the mold along the first gap includes: pouring the silica gel into the mold multiple times, and drying the silica gel after each pouring, and repeating multiple times so that the silica gel is coated on the inner wall surface of the crucible base.
[0110] Specifically, each time the silica gel is poured into the mold, it is dried at room temperature for 20-30 minutes, and dried in a 100°C hot and humid environment for 20-30 minutes. At this time, the silica gel has a certain volume shrinkage, and the silica gel is continued to be poured to fill the first gap. This is repeated many times so that the silica gel is coated on the inner wall surface of the crucible base, and the volume of the silica gel is basically unchanged, then the drying is completed.
[0111] Optionally, before placing the crucible base in the mold and providing a first gap between the mold and the inner wall surface of the crucible base, the method further comprises: performing a surface roughening treatment on the inner wall surface of the crucible base.
[0112] Optionally, the surface roughening treatment of the inner wall surface of the crucible base includes: using a sandblasting method to spray sandblasting particles onto the inner wall surface of the crucible base through compressed air, and removing the residual sandblasting particles on the surface, so that the inner wall surface of the crucible base obtains a certain degree of cleanliness and different roughness, improves its mechanical properties, increases the adhesion between the inner wall surface of the crucible base and the silica coating, and extends the durability of the silica coating.
[0113] It should be understood that the sandblasting particles can be selected from any one of silicon carbide, corundum or quartz sand. In this example, quartz sand is used.
[0114] Optionally, before the inner wall surface of the crucible base is subjected to surface roughening treatment, the method further includes: ultrasonically cleaning and drying the crucible base, thereby removing dirt from the inner wall surface of the crucible base, reducing contamination at the interface between the inner wall surface of the crucible base and the silica coating, and reducing the effect of dirt on the bonding strength between the inner wall surface of the crucible base and the silica coating.
[0115] Embodiment 4:
[0116] Optionally, in the process of ultrasonically cleaning and drying the crucible base, the crucible base is firstly ultrasonically cleaned three times with deionized water and anhydrous ethanol, and then dried at 60° C. for a total of 1 hour.
[0117] Optionally, in the surface roughening treatment of the inner wall surface of the crucible base, compressed air with a pressure of 0.3 MPa is used as a power to spray sandblasting particles with a particle size of 22 meshes at high speed onto the inner wall surface of the crucible base, and the sandblasting particles remaining on the surface are removed.
[0118] Optionally, the specific operation process of pouring the silica gel prepared by any of the above-mentioned silica gel preparation methods into the mold along the first gap is as follows: after pouring the silica gel into the mold each time, dry it at room temperature for 20 minutes, and dry it in a 100°C hot and humid environment for 20 minutes. At this time, the silica gel has a certain volume shrinkage, and continue to pour silica gel to fill the first gap. Repeat this process many times so that the silica gel is coated on the inner wall surface of the crucible base, and the volume of the silica gel is basically unchanged, then the drying is completed.
[0119] Optionally, the crucible substrate coated with silica gel is placed in a heat treatment furnace for heat treatment to melt the silica gel, and the melted silica gel is cooled to form a silica coating on the inner wall surface of the crucible substrate. The specific operation process is: place the crucible substrate coated with silica gel in a muffle furnace, raise the temperature to 200°C at 0.5°C / min, keep it warm for 20 minutes, then raise the temperature to 500°C at 5°C / min, keep it warm for 60 minutes to melt the silica gel, and then naturally cool the melted silica gel to room temperature to form a silica coating on the inner wall surface of the crucible substrate.
[0120] Optionally, the silicon dioxide coating has a thickness in the range of 1 mm.
[0121] Embodiment 5:
[0122] Optionally, in the process of ultrasonically cleaning and drying the crucible base, the crucible base is firstly ultrasonically cleaned three times with deionized water and anhydrous ethanol, and then dried at 80° C., which takes a total of 1.5 hours.
[0123] Optionally, in the surface roughening treatment of the inner wall surface of the crucible base, compressed air with a pressure of 0.5 MPa is used as a power to spray sandblasting particles with a particle size of 30 meshes at high speed onto the inner wall surface of the crucible base, and the sandblasting particles remaining on the surface are removed.
[0124] Optionally, the specific operation process of pouring the silica gel prepared by any of the above-mentioned silica gel preparation methods into the mold along the first gap is as follows: after pouring the silica gel into the mold each time, dry it at room temperature for 25 minutes, and dry it in a 100°C hot and humid environment for 25 minutes. At this time, the silica gel has a certain volume shrinkage, and continue to pour silica gel to fill the first gap. Repeat this process many times so that the silica gel is coated on the inner wall surface of the crucible base, and the volume of the silica gel is basically unchanged, then the drying is completed.
[0125] Optionally, the crucible substrate coated with silica gel is placed in a heat treatment furnace for heat treatment to melt the silica gel, and the melted silica gel is cooled to form a silica coating on the inner wall surface of the crucible substrate. The specific operation process is: place the crucible substrate coated with silica gel in a muffle furnace, raise the temperature to 225°C at 1.2°C / min, keep it warm for 30 minutes, then raise the temperature to 600°C at 8°C / min, keep it warm for 80 minutes to melt the silica gel, and then naturally cool the melted silica gel to room temperature to form a silica coating on the inner wall surface of the crucible substrate.
[0126] Optionally, the thickness of the silica coating is in the range of 2 mm.
[0127] Embodiment 6:
[0128] Optionally, in the process of ultrasonically cleaning and drying the crucible base, the crucible base is firstly ultrasonically cleaned three times with deionized water and anhydrous ethanol, and then dried at 100° C. for a total of 2 hours.
[0129] Optionally, in the surface roughening treatment of the inner wall surface of the crucible base, compressed air with a pressure of 0.6 MPa is used as a power to spray sandblasting particles with a particle size of 40 mesh at high speed onto the inner wall surface of the crucible base, and the sandblasting particles remaining on the surface are removed.
[0130] Optionally, the specific operation process of pouring the silica gel prepared by any of the above-mentioned silica gel preparation methods into the mold along the first gap is as follows: after pouring the silica gel into the mold each time, dry it at room temperature for 30 minutes, and dry it in a 100°C hot and humid environment for 30 minutes. At this time, the silica gel has a certain volume shrinkage, and continue to pour silica gel to fill the first gap. Repeat this process many times so that the silica gel is coated on the inner wall surface of the crucible base, and the volume of the silica gel is basically unchanged, then the drying is completed.
[0131] Optionally, the crucible substrate coated with silica gel is placed in a heat treatment furnace for heat treatment to melt the silica gel, and the melted silica gel is cooled to form a silica coating on the inner wall surface of the crucible substrate. The specific operation process is: place the crucible substrate coated with silica gel in a muffle furnace, raise the temperature to 250°C at 2°C / min, keep it warm for 40 minutes, then raise the temperature to 700°C at 10°C / min, keep it warm for 100 minutes to melt the silica gel, and then naturally cool the melted silica gel to room temperature to form a silica coating on the inner wall surface of the crucible substrate.
[0132] Optionally, the thickness of the silica coating is in the range of 3 mm.
[0133] The embodiment of the present application also provides a crucible, which is prepared by any of the above-mentioned crucible preparation methods, and the crucible includes a crucible base and a silica coating formed on the inner wall of the crucible base by melting and cooling silica gel, wherein a moisturizer and a cross-linking agent are added during the preparation of the silica gel. When a conventional crucible is used to pull a single crystal silicon rod using a continuous straight-pulling method, the content of metal ion impurities such as magnesium, aluminum, yttrium, etc. in the silicon rod can reach more than 100 ppm. By combining the above-mentioned silica gel with the inner wall of the crucible base to form a dense silica coating, this coating can isolate the direct contact between the molten silicon liquid and the crucible base, and block the metal elements and other impurity elements in the crucible base from diffusing into the silicon liquid, so that the metal ion impurities in the silicon rod are reduced to about 10 ppm, which does not affect the production of the silicon rod, and at the same time can extend the service life of the crucible, and the preparation process is simple. In addition, by forming a silica coating on the inner wall surface of the crucible base, there is no need to use a crucible made entirely of quartz. Each crucible prepared can save 20-30 kg of high-purity quartz sand, which can effectively alleviate the current situation of quartz sand supply exceeding demand.
[0134] The embodiment of the present application also provides an application of the above-mentioned crucible in the process of preparing single crystal silicon, by combining the above-mentioned silica gel with the inner wall surface of the crucible base to form a dense silica coating. Therefore, when a single crystal silicon rod is pulled by the continuous straight pulling method, this coating can isolate the molten silicon liquid from direct contact with the crucible base, and block the metal elements and other impurity elements in the crucible base from diffusing into the silicon liquid, without affecting the production of silicon rods. At the same time, the service life of the crucible can be extended, and the preparation process is simple, which can effectively alleviate the current situation of quartz sand in short supply.
[0135] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing silica gel, characterized in that: The method comprises: Preparing a second matrix solution: adding an organic silicon source and deionized water into an organic solvent to form the second matrix solution; Preparing an intermediate solution: adding a moisturizing agent and a cross-linking agent to the second base solution and stirring the mixture to form the intermediate solution; Preparing a mixed solution: adding an acid solution or an alkaline solution for adjusting the pH value of the intermediate solution to the intermediate solution and stirring the mixture to form the mixed solution; Obtaining silica gel: allowing the mixed solution to stand and age to obtain the silica gel.
2. The method for preparing silica gel according to claim 1, wherein Preparing the second matrix solution comprises: Preparing a first matrix solution: mixing the organosilicon source, the organic solvent and the deionized water and stirring them uniformly to form the first matrix solution; The first matrix solution is improved by adding a reinforcing agent to the first matrix solution and stirring the solution evenly to form the second matrix solution, wherein the density of the second matrix solution is greater than the density of the first matrix solution.
3. The method for preparing silica gel according to claim 2, characterized in that: In preparing the first matrix solution, the mass ratio of the organosilicon source, the organic solvent and the deionized water is (25-35): (80-120): (80-120); When the first matrix solution is improved, the mass ratio of the first matrix solution to the reinforcing agent is (185-275): (10-15); and / or, in preparing the intermediate solution, the mass ratio of the second matrix solution, the humectant and the cross-linking agent is (195-290): (2-3): (2-3); And / or, in preparing the mixed solution, an acid solution is added to the intermediate solution to adjust the pH value of the intermediate solution to 1-3.
4. The method for preparing the silica gel according to any one of claims 1 to 3, characterized in that: The organosilicon source is tetraethyl orthosilicate; The organic solvent is anhydrous ethanol or methanol; The moisturizing agent is formamide or glycerin; The cross-linking agent is polyethylene glycol; The acid solution is hydrochloric acid; And / or, the alkaline solution is aqueous ammonia.
5. The method for preparing silica gel according to claim 2 or 3, characterized in that: The reinforcing agent is silicon dioxide or silicon nitride.
6. The method for preparing the silica gel according to any one of claims 1 to 3, characterized in that: In the preparation of the second matrix solution, in the preparation of the intermediate solution, and / or in the preparation of the mixed solution, the stirring temperature is 40-60°C.
7. The method for preparing the silica gel according to any one of claims 1 to 3, characterized in that: In preparing the mixed solution, the stirring time is 6 to 8 hours; And / or, the silica gel is obtained with an aging time of 4 to 6 hours.
8. A method for preparing a crucible, characterized in that: The method comprises: Placing the crucible base in a mold, and allowing a first gap to exist between the mold and the inner wall surface of the crucible base; The silica gel prepared by the method for preparing the silica gel according to any one of claims 1 to 7 is poured into the mold along the first slit for multiple times, and the silica gel is dried after each pouring, and the process is repeated multiple times so that the silica gel is coated on the inner wall surface of the crucible substrate, wherein a moisturizing agent and a cross-linking agent are added during the preparation of the silica gel; The crucible substrate coated with the silica gel is placed in a heat treatment furnace for heat treatment to melt the silica gel, and then the melted silica gel is cooled to form a silica coating on the inner wall surface of the crucible substrate.
9. The method for preparing a crucible according to claim 8, characterized in that: The method of placing the crucible substrate coated with the silica gel in a heat treatment furnace for heat treatment to melt the silica gel, and then cooling the melted silica gel to form a silica coating on the inner wall surface of the crucible substrate comprises: placing the crucible substrate coated with the silica gel in a muffle furnace, raising the temperature to 200-250° C. at 0.5-2° C. / min, keeping the temperature for 20-40 min, then raising the temperature to 500-700° C. at 5-10° C. / min, keeping the temperature for 60-100 min to melt the silica gel, and then naturally cooling the melted silica gel to room temperature to form a silica coating with a thickness of 1-3 mm on the inner wall surface of the crucible substrate.
10. A crucible, characterized in that: The crucible is prepared by the crucible preparation method according to claim 8 or 9, wherein the crucible comprises a crucible base and a silica coating formed on the inner wall of the crucible base by melting and then cooling silica gel, wherein a moisturizer and a cross-linking agent are added during the preparation of the silica gel.